Understanding Psychology - Feldman R. S. (New York St. Louis San Francisco Auckland McGraw-Hill Book Company, 1987)
The Study Guide integrates the P.O.W.E.R. Learning system into a comprehensive review of the text material. Multiple-choice practice tests and essay questions allow students to gauge their understanding of the material. An answer key provides answers to all of the chapter s exercises, including feedback for all multiple-choice items. A list of activities and projects that encourage students to apply psychology to their daily lives is also included. ESL material is also included in this edition.n.
Keywords: 159.9